ANALISA HAMBATAN TOTAL KARENA PERUBAHAN BENTUK CHINE PADA KAPAL PATROLI - Muhammad Satrio Elang Prakoso; Samuel Samuel (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
A patrol ship is a fast ship planning hull type. The planning hull type is a ship designed to reduce wetted surface area at a certain speed to reduce the ship's total resistance. The main function of chine on fast boats is to reduce the hull's wetted surface. Modification of the chine shape can improve the performance of the ship while operating. This research will analyze the effect of using modified chine to improve ship performance. This research uses a numerical method (CFD) which is an overset mesh technique. This method is used to predict the resistance, trim, and heave. The result of CFD simulation in this research indicates that the use of chine can improve total resistance on ships, namely the single chine 10° model. The use of chines on patrol ships can increase trim and heave values.